Encryption selection for WLAN IEEE802.11G - Ahmad, Zahrol Azam (2013)
Wireless local area network (WLAN) has emerged over the past few years and has become a new channel in communication and shared resources. As the utilization of WLAN increased, it is important to study the impact on the performance of WLAN. The performance of this network is always a priority when users want to use this facility. In IEE802.11 WLAN, the users need to ensure the security of their data and the best performance. T he p er fo r ma nc e is always related with the use of encryption protocols. IEEE802.11 contains encryptions protocols that have three major generations, which are wired equivalent privacy (WEP), Wi-Fi protect access (WPA) and counter mode with cipher block chaining Mac protocol (CCMP). However, there are several opinions about the effect of using encryption on the performance of WLAN. A recent study claimed that encryption gives negligible impact to WLAN performance, while other studies showed that it degrades WLAN performance about 20%. Thus, these different findings have motivated this research. As for the solution, it proposes a mechanism of selecting encryption algorithms, which is able to help users to select the suitable encryption algorithm and encryption protocols for their secured communication in IEEE 802.11g WLAN. The impact on throughput and time success can be examined based on encryption algorithms and encryption protocols by using this proposed mechanism. In this study, MATLAB was used for the simulation and the parameters for the simulation were different size of text file, type of encryption algorithms and type of encryption protocols. The data size of text file used were 50 bytes to 300 bytes. The encryption algorithms consist of AES, DES and Blowfish while the encryption protocols consist of WEP, TKIP and AES/CCMP. There were two scenarios that have been tested in the simulation. In the first scenario, the data was tested with encryption protocols and for the second scenario, the data was tested with encryption algorithms and also encryption protocols. Meanwhile for encryption algorithms, the data was encrypted using Kryptel, an encryption freeware. This encryption process occurred before transmitting the data through IEEE802.11 WLAN and encryption protocol at the access point. The results obtained from this simulation were time success and throughput. Through the results, time success was increased in both scenarios, as the data size became larger after it was encrypted. It also showed that DES algorithm produced the best time success along with WEP encryption protocol. As for the throughput, AES algorithm with WEP produced the best throughput in both scenarios, except when the size of data was 300 bytes, the results showed that Blowfish was the best encryption algorithm to be coupled with WEP encryption protocol. Based on the findings, it showed that this proposed mechanism can act as a guide to select which encryption algorithms and encryption protocols that provided in IEEE802.11 standards and also can ensure the best performance in WLAN.